Construcionismo de papert e o ensino-aprendizagem do efeito doppler: um kit didático de robótica com a utilização de um laboratório portátil - SILVA, Valdeci Teles da (2021)
The use of information and communication technologies (ICT's) in the teaching of Physics focuses on the problem of methodology in teaching, attacking the stereotype of a boring, tedious and difficult subject, in addition to contemplating the use of multimedia digital content in the process. of teaching and learning, as well as its influence on changes in teacher practices. This work presents a reflection on the new modalities of reading and writing enhanced in interactive virtual environments and how these processes can be systematized for the classroom. It runs through the theories of Teaching by Inquiry – by John Dewey, and Meaningful Learning, by David Ausubel. The chosen object of study is about teaching the Doppler Effect to elementary school students through educational robotics from the analysis, through graphics, of the Doppler frequency emitted by a sinusoidal sound source at a fixed frequency that is captured by the application installed in a smartphone. In this proposal, all the observation stages of the experiment were carried out by the students with the teacher as an intermediary. The development of this pedagogical proposal allowed us to build a didactic sequence, which began with the application of a questionnaire on sound waves focusing on more general everyday situations that evidenced the Doppler Effect. At that moment, our objective was to have a prior knowledge of how the students interpreted these phenomena to guide the application of the didactic sequence. In a second moment, two classes were given on the Doppler Effect and a questionnaire was applied focusing on more specific situations to find out what the students understood of the exposed content. In the following classes, the experiment of the robotic kit in the schoolyard was presented to the students and a new questionnaire was applied to monitor the evolution of learning. Due to the moment of the covid 19 pandemic, face-to-face classes at the school were interrupted, but we benefited from the “Escola em Movimento” program, which is an initiative supported and fostered by the secretary of education represented by the regional of Barra do Corda, to continue in our planning on the condition that all recommended social distancing recommendations are followed. The didactic sequence was planned from constructionist ideals. After all the steps of the application of this pedagogical proposal and analysis of the devices applied to evaluate the quality of our work together with the increase in student performance and the satisfaction shown by the school administration through full support and encouragement, we consider that the content has been learned. proposed.